Using Comic Strips to Improve Students’ Motivation and Reading Comprehension at MA Raudlatusshibyan NW Belencong - Bq Zuhrotun Nafisah; Aditya Pratama (PALAPA, 2020)
This research was aimed to know how comic strip can improve students’ motivation and reading comprehension at MA. Raudlatusshibyan NW Belencong in academic year 2017/2018. The research design was classroom action research. It consists of one cycle, and the cycle consists of planning, action, observation, and reflection. The data were collected by using reading tests and questionnaire. The result study shown that comic strip improved students’ motivation and reading comprehension. The percentage of students that got very high motivation after using Comic Strip in learning reading is 55% and 45% got high motivation. The result of the mean in post-test at cycle 1 is 77,9 while the students’ highest score was 88 and the lowest score was 52. The result of the test shown the abilities of the students were improved. There were 17 students or 85% out of the 20 students who reached the score of KKM while the rest of them there were 3 students or 15% failed. It is indicated the improvement of student’s reading comprehension and their motivation of English learning process.